The hold-up problem with flexible unobservable investments - Daniel Krähmer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
The paper studies the canonical hold-up problem with one-sided investment by the buyer and full ex post bargaining power by the seller. The buyer can covertly choose any distribution of valuations at a cost and privately observes her valuation. The main result shows that in contrast to the well-understood case with linear costs, if investment costs are strictly convex in the buyer's valuation distribution, the buyer's equilibrium utility is strictly positive and total welfare is strictly higher than in the benchmark when valuations are public information, thus alleviating the hold-up problem. In fact, when costs are mean-based or display decreasing risk, the hold-up problem may disappear completely. Moreover, the buyer's equilibrium utility and total welfare might be non-monotone in costs. The paper utilizes an equilibrium characterization in terms of the Gateaux derivative of the cost function.
Keywords: C61; D42; D82; 330; Information Design; Hold-Up Problem; Unobservable Information